Leading Dragon Phenomenon: New Opportunities for Catch-up in Low-Income Countries - Vandana Chandra; Justin Yifu Lin; Yan Wang (Asian Development Review, 2013)
Modern economic development is accompanied by the structural transformation from an agrarian to an industrial economy. Since the 18th century, all countries that industrialized successfully have followed their comparative advantages and leveraged the latecomer advantage, including emerging market economies such as the People's Republic of China (PRC), India, and Indonesia. The current view is that Chinese dominance in manufacturing hinders poor countries from developing similar industries. We argue that rising labor cost is causing the PRC to graduate from labor-intensive to more capital-intensive and technology-intensive industries. This will result in the relocation of low-skill manufacturing jobs to other low-wage countries. This process, which we call the “leading dragon phenomenon,” offers an unprecedented opportunity to low-income countries. Such economies can seize this opportunity by attracting the rising outward foreign direct investment flowing from Brazil, the PRC, India, and Indonesia into the manufacturing sectors. All low-income countries can compete for the jobs spillover from the PRC and other emerging economies, but the winner must implement credible economic development strategies that are consistent with its comparative advantage.